Chest X-ray findings in HIV infected children starting HAART at a tertiary institution in South Africa - Mahomed, Nasreen (My University, 2013)
INTRODUCTION: There is limited information on the radiographic presentation of children eligible to start HAART in resource-limited settings. OBJECTIVES: Determine radiographic patterns on pre-HAART chest X-rays (CXRs) in children, compare findings in immune-suppressed vs. non immune-suppressed children, compare the percentage of children with radiographic features of pulmonary TB to the percentage of children on TB treatment and assess inter-observer agreement between 3 radiologists. METHODS: Children (0-8 years) participating in a cohort study of TB and BCG-IRIS who had an acceptable routine pre-HAART CXR were included. CXRs were independently assessed by 3 radiologists, blinded from clinical data, using a standardised assessment form. All 3 readings were used to create a majority consensus finding during the data analysis phase. RESULTS: Amongst 161 children, the median age at enrolment was 2.3 years (25% (41/161) were <1year), 54% (87/161) were on TB treatment and 65% (100/154) were immune-suppressed. The majority (71%) had an abnormal CXR finding, predominantly air space disease (42%) and parenchymal interstitial disease (21%). Of the sub-group of 112 (70%) CXRs that could be assessed for lymphadenopathy, 75(67%) had one or more features suggestive of TB (74 lymphadenopathy, 2 cavities, 18 miliary infiltration) and 65% (70/107) were immune-suppressed. Statistically significant differences between immune-suppressed and non-immune-suppressed children were noted for features of lymphadenopathy and radiographic pulmonary TB. Amongst the sub-group of 112 CXRs a high percentage 49/75 (65%) were on TB treatment, with 26/75 (35%) not on TB treatment. Inter-observer agreement between all 3 readers was fair for overall abnormal CXR findings (K=0.23), airspace disease (K=0.22), moderate for parenchymal interstitial disease (K=0.54) and slight for lymphadenopathy (K=0.05). CONCLUSION: Among children eligible to start HAART, most (71%) presented with abnormal CXR findings and the majority (67%) had one or more CXR signs suggestive of TB. Of concern was the high proportion of CXRs (30%) that were of insufficient quality to be assessed for lymphadenopathy and the poor inter-observer agreement for lymphadenopathy.
A research report submitted to the Faculty of Health Sciences, University of Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine in the branch of Diagnostic Radiology Johannesburg, 2013
Keywords: Radiography--in infancy & childhood; Antiretroviral Therapy, Highly Active; HIV Infections--in infancy & childhood